Deconstructing the narrative of power: a critical discourse analysis of Tempo.Co ‘Bagi-bagi konsesi tambang’ in youtube. - Arzeti, Dinda Syakilla Dwi Putri; Elviria, Samia; Muhaimin, Muhaimin; Mairita, Desy; HM, Pahrudin; Maghfirah, Noor Khalida (Fakultas Ilmu Komunikasi UKWMS, 2025)
ABSTRACT This study examining the convergence of textual strategies, newsroom politics, algorithmic infrastructures, and investigates how investigative journalism functions in platformized media environments. The study examines Tempo.co's Bocor Alus Politik episode